The Little Things : A Story About Acts of Kindness - Trimmer, Christian; Juanita, Kaylani (New York, NY : Abrams Books for Young Readers, 2021)
A little girl's small act of kindness after a storm spreads throughout her town so that the next time there is a storm, her community comes together to make a big difference.
Keywords: Kindness -- Juvenile fiction; Community life -- Juvenile fiction; Starfishes -- Juvenile fiction; Storms -- Juvenile fiction; Kindness -- Fiction; Community life -- Fiction; Starfishes -- Fiction; Storms -- Fiction; Picture books